2019
DOI: 10.3390/catal9070622
|View full text |Cite
|
Sign up to set email alerts
|

Dextran Aldehyde in Biocatalysis: More Than a Mere Immobilization System

Abstract: Dextran aldehyde (dexOx), resulting from the periodate oxidative cleavage of 1,2-diol moiety inside dextran, is a polymer that is very useful in many areas, including as a macromolecular carrier for drug delivery and other biomedical applications. In particular, it has been widely used for chemical engineering of enzymes, with the aim of designing better biocatalysts that possess improved catalytic properties, making them more stable and/or active for different catalytic reactions. This polymer possesses a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 315 publications
(383 reference statements)
0
28
0
Order By: Relevance
“…The use of PEI-coated carriers ensures strong ionic interaction with the enzyme, avoiding the limitations typical of covalent immobilization [ 41 ]. Similarly, the use of dextran aldehyde allows the stabilization of enzyme-carrier interactions by crosslinking, preventing the dissociation of enzymatic subunits [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of PEI-coated carriers ensures strong ionic interaction with the enzyme, avoiding the limitations typical of covalent immobilization [ 41 ]. Similarly, the use of dextran aldehyde allows the stabilization of enzyme-carrier interactions by crosslinking, preventing the dissociation of enzymatic subunits [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the intermolecular crosslinking is properly developed to include most of the enzymes in the PCMC, this could give a kind of "empty globe" formed by crosslinked enzyme molecules, which could find many different applications. This massive inter-protein crosslinked may be achieved using dextran aldehyde instead of glutaraldehyde [182], and fully protein loaded PCMC to make easier this crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that just the stirring of the enzymes in the reaction medium promoted an inactivation, which was attributed to the action of shearing force on the enzyme molecules because the enzyme is located on the support surface [175]. This problem is general for any nanomaterial where the enzyme is located on the surface [181] and could be at least partially solved if coating the enzyme molecules with some polymers [181][182][183][184][185].…”
Section: Chemically Crosslinked Pcmcsmentioning
confidence: 99%
“…All the enzymes were used as immobilized biocatalysts according to our previous investigations. Thus, CpUP and AhPNP were used upon covalent immobilization on glyoxyl-agarose [18], whereas DddAK was immobilized by a ionic interaction on an epoxy carrier (Sepabeads ® EC-EP) previously coated with polyethylenimine (PEI), followed by cross-linking with a polyaldehyde (CL) [12,27]. In agreement also with recent reports [25,26], this latter approach results in a sort of "co-immobilization" of the co-factor (ATP, in this case), thus ensuring a self-sufficient source of it for an efficient catalysis.…”
Section: A Three-enzyme Cascade For the Synthesis Of Araa-mpmentioning
confidence: 99%